The impact of the price of a barrel of oil on some of the indicators of economic balance in Algeria During 1986-2011 - Bellaouar, Slimane (Dirassat Journal Economic Issue, 2015)
The Algerian economy is oil economy since many decades, and even now, and is evidenced by the sensitivity of most indicators of economic balance for the price of a barrel of oil, where these indicators and are affected by the direction of change of the price of oil rose and fell. And this study has focused on four indicators: the total exports and the balance of trade balance and GDP and total revenues for the period extending from 1986 to 2011. The study results showed a Long-term equilibrium relationship between Most of the study variables, and there is no short-term equilibrium relationship between Most of the study variables. As well as the study shows there is the impact of a shock change in the price of oil to the rest of the variables, It is evidence that the oscillations that occurred in the value of economic indicators are due to changes in the price of oil.